2018
DOI: 10.1007/s12029-018-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Carcinoma of Gallbladder: A Step Beyond Palliative Therapy, Experience of 25 Cases

Abstract: In carefully selected patients of GB NECs, downsizing with NACT facilitates radical resection with negative margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…4,9,19 Due to its rarity, studies of GB-NEC are mostly case reports and only a few studies were single-center researches with small samples. 11,[13][14][15]20 Therefore, the data to evaluate the clinicopathological characteristics are limited. In our study, 15 patients with GB-NEC from two well-known tertiary medical centers were included, which makes it one of the largest series of GB-NEC in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,19 Due to its rarity, studies of GB-NEC are mostly case reports and only a few studies were single-center researches with small samples. 11,[13][14][15]20 Therefore, the data to evaluate the clinicopathological characteristics are limited. In our study, 15 patients with GB-NEC from two well-known tertiary medical centers were included, which makes it one of the largest series of GB-NEC in China.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, once diagnosed, extensive surgery and careful follow-up are mandatory and radical surgical resection is thought to be the relatively optimal treatment while medical therapy will be favorable in high grade metastatic carcinomas. [10][11][12][13] However, current treatment strategies cannot prevent patients from poor prognosis and overall survival time varied from 4 to 13.7 months, 11,14,15 which was significantly worse than gallbladder adenocarcinoma (GB-ADC), the most common carcinoma of gallbladder. In this report, we introduced and analyzed 15 patients with gallbladder neuroendocrine carcinoma (GB-NEC) treated in two tertiary medical centers in The People's Republic of China between 2009 and 2015, then we compared them with patients of GB-ADC using a propensity score analysis and discussed their clinicopathological features and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Included studies. A total of 15 studies (14 case reports and 1 case series), which comprised 19 patients who successfully underwent surgical treatment for gMANEC were considered eligible for inclusion and analysis in our systematic review as shown in Table I (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative diagnosis of gallbladder carcinoma was established in six (31.5%) cases; in four of them preoperative biopsy was utilized (14,17), while in the other four PET and endoscopic ultrasound (EUS) were used (26,28). Considering the locally advanced stage of disease at the time of diagnosis, two patients (10.5%) received preoperative neoadjuvant chemotherapy with favorable response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation